2019
DOI: 10.3386/w25527
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Effects of Welfare Reform: Adolescent Delinquent and Risky Behaviors

Abstract: for helpful comments, to the staff at the University of Michigan's NADHAP for their data and technical help, and Michael Papotto for excellent research assistance. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Over 36 million children have at least one parent with a criminal record (Thompson, 2019). Recent research indicates that the welfare reform that took place in the 1990's resulted in increases in delinquent behavior of the children impacted by these changes, as well as increases in substance use of both boys and girls (Dave et al, 2021). We expect that the impact of collateral consequences will similarly not be limited to those that are directly impacted, but also to their children.…”
Section: Discussionmentioning
confidence: 99%
“…Over 36 million children have at least one parent with a criminal record (Thompson, 2019). Recent research indicates that the welfare reform that took place in the 1990's resulted in increases in delinquent behavior of the children impacted by these changes, as well as increases in substance use of both boys and girls (Dave et al, 2021). We expect that the impact of collateral consequences will similarly not be limited to those that are directly impacted, but also to their children.…”
Section: Discussionmentioning
confidence: 99%
“…Dave et al. (2021) showed similarly negative results from welfare reform which increased maternal employment on adolescent social behavior, such as less volunteering, skipping school, damaging property, fighting, smoking, and drug use. Unlike preschool‐aged children, low‐income adolescents do not respond positively to policy‐driven increases in maternal employment, especially among those with younger siblings (Hsueh & Gennetian, 2011).…”
Section: Overarching Themes In the Literaturementioning
confidence: 95%
“…Hsueh and Gennetian (2011) showed that policy-induced maternal employment which does not increase income but does increase sibling care is associated with poor adolescent school outcomes such as performance, suspension, and expulsion. Dave et al (2021) showed similarly negative results from welfare reform which increased maternal employment on adolescent social behavior, such as less volunteering, skipping school, damaging property, fighting, smoking, and drug use. Unlike preschool-aged children, low-income adolescents do not respond positively to policydriven increases in maternal employment, especially among those with younger siblings (Hsueh & Gennetian, 2011).…”
Section: Heterogeneous Effects By Children's Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations